An Analysis of Polish Teachers Attitudes towards Inclusive Education - Anna Czyż (International Society of Philosophy and Cosmology, 2018)
The purpose of the study was to determine the relation to inclusive education involving teachers of both public and special schools. The study was conducted on a sample of 224 teachers. In the study, a diagnostic survey was used with the Scale for Measuring Attitudes towards Inclusive Education. The tool was designed for the purposes of this study and it was analyzed for internal consistency and reliability. A key for the attitudes' verification was established and it is based on a sten scale. The measured values were treated as the basis for ordering the material in the direction of the attitude. The findings show the neutral attitude in the tested sample and there is no difference observed based on the type of represented school.